Helical Computed Tomography has a Role in the Screening of Lung Cancer – The Pro Argument. Issue 3 (3rd April 2004) - Patel, Milan
Abstract : In 2003, approximately 21, 000 new cases of lung cancer were diagnosed across Canada. Nearly 19, 000 Canadians died of this devastating disease that year (1). Worldwide, there are over one million cases identified annually (2). In the Western world, more patients die of lung cancer than from breast, prostate and colon cancer combined. Despite these figures, lung cancer has remained low on the health care agenda. In the past three decades, there has been little improvement in observed lung cancer survival rates, with overall five-year survival rates approaching 15% (3).